Evaluation of Procalcitonin Diagnostic Accuracy with Comparison to Blood Culture - Yasir Ali Bhatti, Sadia Zia, Hooria Aamir, Zulfiqar Ali Memon, Afshan Akbar, Muhammad Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Procalcitonin has been used globally as indicator marker of sepsis to define bacteremia or blood stream infection for early patient management or antibiotic therapy. Blood culture refers to a microbiological culture of a peripheral blood sample. The blood cultures help to determine the presence of systemic infections, such as septicaemia. If the culture is positive, the causative micro-organism can usually be identified, and antibiotic sensitivity testing performed. On the other hand, the sensitivity of procalcitonin in comparison to its specificity to certain bacterial infections is still in question. Methodology: In this study, we selected 309 patients without restriction of age gender with pre-diagnosed sepsis or septic shock syndrome. Blood culture samples were collected in bactAlert media plus culture bottles and were incubated in BactAlert 3D semi-automated blood culture system; blood sample was collected for serum procalcitonin on immunoassay principle. Results: Out of 309, a total 87 blood cultures were positive and PCT was positive in 134 whereas 179 were PCT negative. In positive PCT, 63 were having bacterial growth in their blood culture while 71 were with negative blood culture. Although in total, 179 PCT were negative, only 16 were having bacterial growth in blood culture samples whereas all others revealed no growth that showed maximum number of positive blood cultures were having PCT positive but not all PCT positive demonstrated bacterial growth in blood culture suggesting that the bacteremia or sepsis can only be suspected with positive PCT. In addition, blood culture positive or negative results cannot be predicted by PCT value to make diagnostic confirmation of sepsis.